The problem of methodological identity in Croatian conservation community, 1945-1964 - Špikić, Marko (Array, 2014)
: The paper discusses three problems: reception of European conservation concepts, their relevance, survival and application in the period of a significant social change, and relationships between this theoretical tradition and restoration practice in early socialist Croatia. It has become quite common in the past two decades to discuss the importance of the European conservation theory created around 1900 for our contemporary dilemmas. The relevance of those concepts for our times may not be a symptom of nostalgia, but of contemporary crisis or lack of methodological identity, at least on the national level. The significance of Boito’s, Riegl’s, Giovannoni’s, Dvořák’s, Gurlitt’s and Dehio’s ideas therefore is not only important for the arising genre of conservation historiography or building of the national conservation canons. Their re-appropriation opens new potentials for understanding of 20th-century history of conservation ideas which was marked by significant discontinuities due to the abrupt social and political changes. The fate of these paradigms can be compared with history of societies where they supposed to gain an important place in a battlefield of expert, political and social approaches to collective memory. Croatia after 1945 became one of the six (first “people’s”, than “socialist”) republics. Following the disasters of war – experience of the Holocaust, the division among political tribes and destruction of monuments and sites – Croatian conservators faced a new era. This was not only in a political, but also methodological sense, since the generation of men and women employed in conservation after 1945 still followed the models of Austrian Central Commission and German Heimatschutz movement that simultaneously motivated patriotism and democratization of perception. The paper therefore deals with the fate of these legacies at the beginning of socialist period in Croatia. This is discussed bearing in mind the appearance of other approaches and paradigms, such as Polish and Italian experiences of reconstruction after the Second World War. That lead to further inquiries: what is the relationship between the reception of Central-European principle of konservieren nicht restaurieren and of the post-war Italian definitions of restauro critico? What is the political and social significance of the restoration principle in Croatia after 1945? Did reconstruction and renovation of monumental settings mean introduction of a new, “active” or “interventionist”, paradigm, therefore a turn in the country’s conservation tradition? Last but not least, presentation discusses the relevance of this period’s experiences for the conservation community in today’s Croatia